Study of serum cholesterol binding reserve and cholesterol levels in myocardial infarction patients at tertiary Care hospital from central India - Dr. AMIT SINGH RAY,; Dr. KRISHNA MURARI, (International Journal of Pharma and Bio Sciences, 2017)
Myocardial infarction is most common cardiovascular disorder. It occurs due to coronary artery disease. It is leading cause of death in elderly people in India. Increased serum cholesterol plays an important role in etiopathogenesis of myocardial infarction. Serum cholesterol binding reserve is the capacity of serum to solubilise additional cholesterol.To estimate the serum cholesterol and serum cholesterol binding reserve in myocardial infarction patients and its association with disease activity. A case control study was conducted on 60 clinically diagnosed cases of myocardial infarction patients and 60 age and sex matched healthy controls. Blood samples were collected from each study subjects and analyzed for serum cholesterol and serum cholesterol binding reserve. Serum cholesterol was found to be significantly (<0.001) higher (282.10±75.78 mg/dl) in myocardial infarction patients as compare to healthy control (187.76±20.58 mg/dl). Whereas serum cholesterol binding reserve significantly (<0.001) decreased (19.40±5.58 mg/dl) in myocardial infarction patients as compare to healthy control (59.05±6.22 mg/dl).We concluded that levels of serum cholesterol are higher and cholesterol binding reserve value were lower in myocardial infarction patients as compare to normal healthy controls.